ПАРЛАМЕНТ ДАХЬ ЭМЭГТЭЙЧҮҮДИЙН УЛС ТӨРИЙН ОРОЛЦОО - Б.Одгэрэл (Politology, 2023)
First Democratic states face up to women’s political rights in nineteenth century.Therefore women’srepresentationis increased in Legislatures around the world. Today, there are 20.4% of legislature houses, are women. In order to improve women’srepresentation in the legislature is to have awoman quotation mechanism. In 2012,MongolianGreat State Khuralpasses new law about Election. According new election law,more than 20% of candidates are must be woman from all political parties. By consequence of the law, first time in democratic election history of Mongolia, woman members became 14.5% of Great State Khural. However, We need toincrease women’s representation in legislature in Mongolia.In order to so, we have tochange the human resource policy and raisewomen representation in decision making of all political parties. Хураангуй: Шийдвэр гаргах түвшинд эмэгтэйчүүдийн оролцоог тодорхойлох харьцууллын аргыг түлхүү хэрэглэсэн энэхүү судалгааны өгүүлэлдээ дэлхий дахины хууль тогтоох байгууллага дахь эмэгтэйчүүдийн төлөөллийнтоо, эзлэх хувийг харьцуулан, улс орнуудын хууль тогтоох байгууллагад эмэгтэйчүүдийн төлөөллийг оруулж буй арга механизмыг судлаж, Монголын эмэгтэйчүүдийн шийдвэр гаргах түвшний оролцооны цаашдын чиг хандлагыг тогтоохыг зорьсон билээ.